Rethinking Contemporary Library Environment as a Social Learning Centre - Rauf, Hozan Latif (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In the era of digitalization and dominance of Internet search, student needs related to contemporary academic library spaces have changed. In search of ways for answering these changing needs of students, most universities have started to transform their spaces. Architects and interior architects/designers have done little research to guide such a transformation. This study aims to overcome this gap by thoroughly examining and analysing existing literature and providing an in-depth investigation on Eastern Mediterranean University main library as a case. The research design is a “mixed methods” one, involving the combination of qualitative and quantitative research and data in the study. It starts as a qualitative one with onsite observations and informal interviews. The outcomes from this phase are used to construct the second quantitative phase at which the data are collected through structured questionnaires. The results reveal that, EMU main library does not fully coincide with the essential characteristics for contemporary academic libraries. The criteria of this research could be used as guidance for evaluating academic libraries, which need a transformation. As a conclusion, the study provides some suggestions to help EMU main library re-define its spaces and to reclaim its place on the campus.

ÖZ: Dijitalleşme ve internette arama egemenliği çağında, kütüphane mekanları ile ilişkili çağdaş gereksinimler de değişti. Şimdi, sıklıkla, birçok kütüphane kullanıcılarına son zamanlarda “öğrenim müşterekleri (ortak faydalandığımız öğrenim alanları)” şeklinde de ifade edilen konforlu mekanlar sunmak üzere kendini yenileme sürecindedir. Doğu Akdeniz Üniversitesi’nin merkezi kütüphanesi de benzer bir anlamda yenilenme sürecine girmesi gerekmektedir. Halbuki, şu anda, böylesi bir dönüşümü yönlendirebilecek nitelikte bir çalışma yoktur. Bu araştırma, mevcut literature derinlemesine tarayarak ve öğrencilerden de bilgi toplayarak bu açığı kapatmayı amaçlamaktadır. Araştırma tasarımı, çalışma sürecinde, nitel ve nicel araştırma ve veri kombinasyonlarını içeren "karma yöntemler" üzerine dayandırılmıştır. Araştırma, yerinde yapılan gözlemler ve açık uçlu görüşmelerle, nitel bir çalışma olarak başlar. Bu aşamanın sonuçları, ikinci, nicel araştırma fazını oluşturmak için kullanılır. Bu bölümde, veriler yapılandırılmış anketler aracılığıyla toplanmıştır. Sonuçlar, DAÜ merkezi kütüphanesinin, çağdaş kütüphane özellikleri ile tam olarak örtüşmemekte olduğunu ortaya koymaktadır. Bu araştırma kapsamında kullanılan değerlendirme kriterleri diğer başka dönüşüm ihtiyacı içinde olan akademik kütüphaneler için de kullanılabilir. Sonuç olarak bu çalışma, DAÜ merkezi kütüphane alanlarının yenilenmesi ve bu kütüphanenin kampüsteki önemli yerini yeniden geri kazanması için yardımcı olabilecek bazı somut öneriler sunar.
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2016. Supervisor: Assist. Prof. Dr. Münevver Özgür Özersay.
Keywords: Interior Architecture; Interior Design; Library Architecture--Library Buildings; Architecture, Modern--Academic Libraries; Modern University Libraries--Architecture and Design; Contemporary academic libraries; transformation; interior space characteristics; social learning space characteristics